A novel fault protection system using communication-assisted digital relays for AC microgrids having a multiple grounding system. (June 2016) - Lien, Keng-Yu; Bui, Duong Minh; Chen, Shi-Lin; Zhao, Wei-Xiang; Chang, Yung-Ruei; Lee, Yih-Der; Jiang, Jheng-Lun
Highlights: Develop a novel fault protection system for multiple-grounded AC microgrids. Reconfigure microgrid structures into a standard multiple-grounded AC microgrid. Existing fault protection modules are used for microgrids at a grid-connected mode. A developed FDA fault protection module to protect microgrids at an islanded mode. PSCAD simulation and real-time experiment results are analysed and discussed. Abstract: This paper develops a novel fault protection system for AC microgrids having a multiple grounding system. Communication-supported digital relays which have different protection modules are used for this novel microgrid protection system. The protection modules in a digital relay have various functionalities to protect AC microgrids from various fault types, such as: low/high-impedance ground faults and short-circuits. To effectively use the developed novel microgrid protection system, the first step is to reconfigure different microgrid structures into a standard microgrid configuration having a multiple-grounding system through using delta/wye-grounded or wye-grounded/wye-grounded transformers. Then, a fast–dependable–adaptable (FDA) fault protection algorithm is developed to protect AC microgrids from faults occurring at trunk lines, common buses or branch lines. At an islanded operation mode of AC microgrids, by using digital relays, a new protection module is designed to detect, locate, and classify the faults occurring at trunk lines and common AC buses, while other protection modules can use the existing protection methodologies (e.g. directional/non-directional overcurrent protection principles, etc.) to detect and clear the faults at source branches or load branches of the microgrids. At a grid-connected operation mode, standard overcurrent protection modules are applied for the FDA fault protection system. Simulation and experiment results obtained from various fault cases at a real low-voltage AC microgrid have validated the effective operation of the FDA fault protection system.